2013
DOI: 10.1086/670626
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections, International Nosocomial Infection Control Consortium (INICC) Report, Data Summary of 30 Countries, 2005–2010

Abstract: SSI rates were higher for most SPs in INICC hospitals compared with CDC-NHSN data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 21 publications
2
94
1
6
Order By: Relevance
“…a study conducted between 2005 and 2010 in 30 developing countries, including Brazil, by the International Nosocomial Infection Control Consortium (INICC) found that the mean rate of SSI after cardiac surgery was 5.6%. 11 That rate was significantly higher than the 1.3% reported in a CDC/NHSN study conducted in the United States (rr 4.32; 95% CI 3.81-4.88; P = 0.0001). 11 …”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…a study conducted between 2005 and 2010 in 30 developing countries, including Brazil, by the International Nosocomial Infection Control Consortium (INICC) found that the mean rate of SSI after cardiac surgery was 5.6%. 11 That rate was significantly higher than the 1.3% reported in a CDC/NHSN study conducted in the United States (rr 4.32; 95% CI 3.81-4.88; P = 0.0001). 11 …”
Section: Discussionmentioning
confidence: 66%
“…11 That rate was significantly higher than the 1.3% reported in a CDC/NHSN study conducted in the United States (rr 4.32; 95% CI 3.81-4.88; P = 0.0001). 11 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…tarafından yürütülen, Türki-ye'nin de içinde bulunduğu, Asya, Afrika, Avrupa ve Amerika'yı kapsayan çok merkezli prospektif khort çalışmasında, toplam 260,973 cerrahi prosedürden 7.523 hastada (% 2,3) YYE gözlenmiştir. 5 Sezaryen sonrası YYE oranları %3-5 arasında değişmektedir. 6,7 Bizim çalışmamızda, sezaryen sonrası YYE her iki grup için %1,8 olarak bulunmuş, postoperatif erken dönemde banyo yapabilen ya da insizyon hattı kapalı ve kuru bırakılan gruplar arası anlamlı fark saptanmamıştır.…”
Section: Discussionunclassified
“…6 In high income countries, approximately 2% of surgeries are affected by SSIs. 7,8 World Health Organization (WHO) shows that SSIs are most frequently reported type of HAI in low and middle-income countries (LMICs) with a pooled incidence of 11.8 episodes of SSI per 100 surgical procedures. 9 In India, the risk of acquiring SSI is high (range, 4%-30%).…”
mentioning
confidence: 99%